IbM Pengendalian Hama Terpadu (PHT) pada Tanaman Sayuran di Kota Tomohon - Christina L. Salaki; Sherlij Dumalang (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
An integrated pest control on vegetables crops in the fields,  is one of the control method to suppress the insect pest population , therefore farmer do not depend on the chemical controls that have negative effect both on the environment and human as well as animal.  The science and technology program for communities [IbM] aim to get a package of integrated pest control technology that is enviromentally friendly and it is derived from Indonesian microbial resources to support sustainable agriculture system .  To achieve  the goal, the program  implemented  through counseling, plot demonstration and field work.  These activities provided motivation  to farmers to be able to use biological agents combined with culture control to suppress population of insect pest and vegetables through the extension activities and the plot  demonstrations.  The IbM activity gave benefit to farmers by transfer knowledge through extension methods on how to get and use biopesticides with its theory and it can be directly practiced by farmers in the form of a plot demonstrations.